2020
DOI: 10.1097/fad.0000000000000045
|View full text |Cite
|
Sign up to set email alerts
|

Apixaban-induced leukocytoclastic vasculitis

Abstract: Introduction: Drug-induced vasculitis is a rare adverse drug reaction and the potential to induce such a reaction is often established postmarketing. Leukocytoclastic vasculitis -a subtype of drug-induced vasculitis -often presents itself with palpable purpuric lesions, and often within weeks of initial administration. Case-description: We present a 62-year-old male who presented with leukocytoclastic vasculitis within the first 8 days of apixaban-initiation. Symptoms improved upon discontinuation and resolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Some reports have shown that discontinuing the DOAC without substitution (e.g., in cases of rivaroxaban‐induced leukocytoclastic vasculitis) has not resulted in negative clinical outcomes. 11 There are reports regarding switching from apixaban to warfarin in a case of cutaneous leukocytoclastic vasculitis, 12 anaphylactic reaction, 10 and acute generalized exanthematous pustulosis. 13 Moreover, several reports exist regarding the successful switch from rivaroxaban to low molecular weight heparin (LMWH) in the case of generalized rash 14 maculopapular erythematous and itchy rash, 15 and anaphylactic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that discontinuing the DOAC without substitution (e.g., in cases of rivaroxaban‐induced leukocytoclastic vasculitis) has not resulted in negative clinical outcomes. 11 There are reports regarding switching from apixaban to warfarin in a case of cutaneous leukocytoclastic vasculitis, 12 anaphylactic reaction, 10 and acute generalized exanthematous pustulosis. 13 Moreover, several reports exist regarding the successful switch from rivaroxaban to low molecular weight heparin (LMWH) in the case of generalized rash 14 maculopapular erythematous and itchy rash, 15 and anaphylactic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the patient was started on apixaban at the time of diagnosis of her prothrombin mutation, additional consideration must be given to the possible contribution of apixaban to the development of this patient's rash. Apixaban has been rarely reported to cause leukocytoclastic vasculitis, [6][7][8] as well as a psoriasiform rash. 9 In all of these cases, the patients' cutaneous symptoms arose within 1-2 weeks of starting apixaban.…”
Section: Your Diagnosis?mentioning
confidence: 99%